A brief review of the science behind the design of healthy and sustainable plant-based foods - David Julian McClements; Lutz Grossmann (npj Science of Food, 2021)
Abstract People are being encouraged to consume more plant-based foods to reduce the negative impacts of the modern food supply on human and global health. The food industry is therefore creating a new generation of plant-based products to meet this demand, including meat, fish, egg, milk, cheese, and yogurt analogs. The main challenge in this area is to simulate the desirable appearance, texture, flavor, mouthfeel, nutrition, and functionality of these products using healthy, affordable, and sustainable plant-derived ingredients, such as lipids, proteins, and carbohydrates. The molecular and physicochemical properties of plant-derived ingredients are very different from those of animal-derived ones. It is therefore critical to understand the fundamental attributes of plant-derived ingredients and how they can be assembled into structures resembling those found in animal products. This short review provides an overview of the current status of the scientific understanding of plant-based foods and highlights areas where further research is required. In particular, it focuses on the chemical, physical, and functional properties of plant ingredients; the processing operations that can be used to convert these ingredients into food products; and the science behind the creation of some common plant-based foods, namely meat, egg, and milk analogs.